Homocystinuria in Children - Alexander A. Baranov; Leyla S. Namazova-Baranova; Tatyana E. Borovik; Tatyana V. Bushueva; Oksana V. Globa; Natalya V. Zhurkova; Elena A. Vishneva; Ekaterina Yu. Zakharova; Natalya G. Zvonkova; Ljudmila M. Kuzenkova; Sergey I. Kutsev; Svetlana V. Mikhaylova; et al. (Вопросы современной педиатрии, 2018)
Homocystinuria is a genetically heterogeneous hereditary disease from the group of aminoacidopathies caused by a metabolic disorder of  sulphur-containing amino acids, primarily methionine. The article  presents the etiopathogenetic, diagnostic and therapeutic aspects of this disease and covers modern opportunities of biochemical and molecular  diagnostics. The approach to dietary and pharmacological correction of  metabolic disorders in homocystinuria and the general strategy of  patients’ management are described in detail. Important information is given for physicians of various disciplines and parents of patients.